FLOOD CONTROL CHALLENGES: UNDERSTANDING CAUSES AND EFFECTIVE SOLUTIONS - Femiak, Volodymyr; Сherniuk Volodymyr; Vovk, Lesya (European Science, 2024)
This study addresses the pressing issue of flooding in the context of ongoing climate change, with a particular focus on flood-prone areas in Ukraine. It conducts a comprehensive analysis of both natural and human-induced factors contributing to flooding,